2m/m+3/m=1

Simple and best practice solution for 2m/m+3/m=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m/m+3/m=1 equation:


D( m )

m = 0

m = 0

m = 0

m in (-oo:0) U (0:+oo)

3/m+(2*m)/m = 1 // - 1

3/m+(2*m)/m-1 = 0

3*m^-1 = -1 // : 3

m^-1 = -1/3

-1 < 0

1/(m^1) = -1/3 // * m^1

1 = -1/3*m^1 // : -1/3

-3 = m^1

m = -3

m = -3

See similar equations:

| 1/9y+1/3=-2/27 | | 14x=37 | | y=4(x-7)+6 | | 0.005(x+3)=0.006x+0.011 | | -2(x-4)=13 | | 5x-10x-2x=18 | | 2+(-4)+(-x)-4-(-1)=(-2)+(-x)-4 | | 2(x-b)=x | | 3n+8.8=29.8 | | 2x+21x+28=97 | | 44=4x+4x+9 | | -7-2(m)+1/2(m)=4(m)-10 | | 6x-8=8x+8 | | -2/3(2x+9)=1/3(-4x-54)+12 | | x+5/(x-5)=5+5/(x-5) | | -x+11=-3.4+x | | 1/x-1=7/x+5 | | 9+3z=6(z-1) | | 8+15a=11 | | 3[2(x-1)-x]=5(x+2) | | 2x16/3 | | 2(x+8)=2(4x-4) | | (15)a/25a | | log[10](9x-3)=3 | | -1/4y=-5/24 | | -4(2x-5y)-3x+4y= | | 3/n=15/25 | | 4x+1-2x+7= | | -8(8-x)=.80(x+10) | | 5/x-7=12 | | -15m=0 | | 4.5m+22=49 |

Equations solver categories